Marriage in the Melting Pot: An Evolutionary Approach to European Ancestry, Homogamy, and Fertility in the United States - Schahbasi, Alexander; Huber, Susanne; Fieder, Martin (Frontiers in Psychology, 2022)
To understand marriage patterns, homogamy and fertility of women of European ancestry in the United States from an evolutionary perspective we aim to investigate if a prevalence for ancestral homogamy exists, the factors influencing female preferences and the impact on fertility. Furthermore we aim to determine the heritability of homogamous vs. heterogamous marriage behaviour. We used the census data of 369,121 US women married only once and aged between 46 and 60 years, provided by IPUMS USA (https://usa.ipums.org/usa/). We used linear mixed models to determine associations of the probability of a homogamous vs. heterogamous marriage and the individual fertility of a women. We aimed to estimate the heritability (in terms of genetic & parental environment) of marriage behaviour using a linear mixed model. We found, that ancestral heterogamous marriages are more frequent (56.5%), compared to homogamous marriages (43.5%). Most of the variance in inter-ancestry marriage and fertility is explained by ancestry per se, followed by the ratio of individuals of a certain ancestral background in a county: the more individuals of a certain ancestry live in a county the lower is the tendency to marry someone of a different ancestral background. Furthermore we found that about 11.8% of the marriage behaviour is heritable. Being in a homogamous marriage as well as the income of the spouse are both significantly positively associated with the number of children a women has and the probability that a women has at least one child. The most important explaining factor (in terms of variance explained) for being in an ancestral homogamous vs. heterogamous marriage, for number of children, as well as childlessness is the ancestry of the women. Albeit we are not able to distinguish the genetic and social heritability on the basis of our data, with a total value of 11.8% variance explained only a small heritability for in-group vs. out-group marriage behaviour is indicated.